Respuesta :

gmany

Answer:

(x - 4)(x + 3) = x² - x - 12

Step-by-step explanation:

Use FOIL: (a + b)(c + d) = ac + ad + bc + bd

(x - 4)(x + 3) = (x)(x) + (x)(3) + (-4)(x) + (-4)(3)

= x² + 3x - 4x - 12          combine like terms

= x² + (3x - 4x) - 12

= x² - x - 12

Answer:

Step-by-step explanation:

You have a dangling bracket. I'm not sure what to make of it. I will solve it as

(x - 4)(x + 3) if this is not correct, could you leave me a note.

x^2 + 3x - 4x - 12

x^2 - x - 12

If you meant

(x - 4(x + 3)) then it would be solved as

x - 4x - 12     combine the xs

-3x - 12

dangling brackets are to math what dangling modifiers are to English.

Running up a tree, I saw a squirrel.

If you mean anything but that you were running up a tree, the sentence is incorrect.